PENGARUH KUALITAS SUMBER DAYA MANUSIA, PSIKOLOGI ATLET TERHADAP PRESTASI ATLET DI KOTA PAYAKUMBUH DENGAN MOTIVASI BERPRESTASI SEBAGAI VARIABEL MODERASI - Fitria, Dian; Putri, Anne (Ensiklopedia of Journal, 2024)
Motivation plays a very important role in determining athlete performance. This achievement does not happen instantly, but requires sacrifice, hard work and consistent dedication from the athlete. Athletes who have quality human resources are more likely to overcome obstacles and achieve high achievements. This research aims to analyze the influence of the quality of human resources, athlete psychology on sports performance with achievement motivation as a moderating variable. The population in this study were outstanding athletes in Payakumbuh City. This research uses quantitative methods with primary data in the form of a questionnaire with a total research sample of 80 respondents taken based on sampling techniques. The data analysis technique used is descriptive analysis and inferential statistical analysis with Structural Equation Modeling (SEM) analysis of various Partial Least Square (PLS) variants. Measurement model or outer model, structural model test or inner model, and hypothesis testing with the help of Smart-PLS 4.0 software as a testing tool. The results of this study show that the quality of human resources has a positive and significant effect on athlete performance, athlete psychology has a positive but not significant effect on athlete achievement. Meanwhile, achievement motivation has a negative and significant effect, moderating the influence of human resource quality on athlete achievement, and achievement motivation has a positive but not significant effect, moderating the influence of athlete psychology on athlete achievement. Keywords: Quality of Human Resources, Athlete Psychology, Athlete Achievement, Achievement Motivation